Indoor radon monitoring in selected fault zones, Slovakia – preliminary results from the summer monitoring period - SMETANOVÁ, Iveta; MOJZEŠ, Andrej; MARKO, František; FEKETE, Kamil; CSICSAY, Kristián (Contributions to Geophysics and Geodesy, 2019)
Indoor radon survey in Sološnica, Vydrník and Zázrivá villages has been performed within the framework of the project “Multidisciplinary research of geophysical and structural parameters, and environmental impacts of faults of the Western Carpathians”. Integration measurement of 222Rn activity concentration has been carried out using RamaRn detectors in houses, offices, schools and kindergartens. Indoor radon activity in the summer monitoring period (June–August 2018) varied from values under the detection limit of 55 Bq/m3 to 480 Bq/m3. In 94% of rooms the radon activity below 200 Bq/m3 was found. The results have been examined in respect of the most used building material and presence or absence of a cellar underneath the room. Indoor radon higher than 300 Bq/m3 was measured only in rooms in direct contact with the subsoil.